2012
DOI: 10.1084/jem.20120058
|View full text |Cite
|
Sign up to set email alerts
|

Reduced TCR signaling potential impairs negative selection but does not result in autoimmune disease

Abstract: TCR signal attenuation selectively favors Foxp3 expression and T reg cell lineage commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 59 publications
(105 reference statements)
9
52
0
2
Order By: Relevance
“…Therefore, it is possible that dysregulation of both positive and negative selection in SATB1cKO mice is also caused by weak TCR signal strength at the DP stage. However, it has been reported that symptoms of autoimmune diseases are not observed in TCRz mutant mice because of increased numbers of Foxp3 + Treg cells (53). SATB1cKO mice have impairment of Treg functions compared with WT mice at adulthood (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is possible that dysregulation of both positive and negative selection in SATB1cKO mice is also caused by weak TCR signal strength at the DP stage. However, it has been reported that symptoms of autoimmune diseases are not observed in TCRz mutant mice because of increased numbers of Foxp3 + Treg cells (53). SATB1cKO mice have impairment of Treg functions compared with WT mice at adulthood (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…6A, 6C, 6E, 6F). A very recent study (48) of mutant CD3z-chain knockin mice indicated that attenuation of TCR proximal signaling disproportionately impairs downstream signaling responses and subsequently favors Foxp3 expression and T reg lineage commitment. Consistent with this result, in our study, additional expression of transgenic Pep attenuated TCR proximal signaling and downstream Akt and Foxo1 activation in T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…c-Cbl −/− mice were provided by J. Chiang (National Cancer Institute, Bethesda, MD). Themis1 −/− (5), Themis1-tg (9), Grb2 +/− (33), TCRz 6Y/6Y (46), and TCRz 6F/6F (46) mice were described previously. The AND and OT-2-TCR transgenic mice were obtained from Taconic Farms.…”
Section: Micementioning
confidence: 99%